Labor Force Migration, Unemployment and Job Turnover - Fields, Gary S. (The Review of Economics and Statistics, 1976)
[Excerpt] In this paper, we show how labor turnover considerations can be integrated into the human investment theory of migration and demonstrate that such a model provides a much better explanation for migration rates into major metropolitan areas than the conventionally-used unemployment rate. The method used here may be of interest as well to researchers working on other human investment problems that also have a multi-period dimension.